Multifocal Pulmonary Granular Cell Tumor Presenting with Postobstructive Pneumonia - Samid M. Farooqui; Muhammad S. Khan; Laura Adhikari; Viral Doshi (Case Reports in Pulmonology)
Granular cell tumor (GCT) is a neoplasm of Schwann cell origin. Its presence in the aerodigestive tract is uncommon and becomes a diagnostic challenge on initial presentation. Our case is of a 59-year-old woman who presented to the emergency department with a history of productive cough and dyspnea associated with fever and chest pain. An initial chest X-ray (CXR) showed a right middle lobe consolidation with follow-up Computed Tomography (CT) scan showing a mass in the right bronchus. Bronchoscopy revealed a polypoid, sessile granular mass in the right bronchus intermedius with multiple white lesions in trachea, left main bronchus, and right upper bronchi. Histology revealed a benign GCT. Bronchoalveolar lavage from the right middle lobe grew Streptococcus pneumoniae. Patient was treated with intravenous levofloxacin during hospital stay and discharged on a 7-day course of oral antibiotics to be followed as outpatient but was lost to follow-up. GCT can present as a polypoid tumor causing recurrent postobstructive pneumonia. Surgical resection is the most successful treatment option. The tumor is more common in third and fourth decade of life and our patient is the oldest patient, according to our knowledge, to have a GCT.